A Systematic Review of U.S.-Based Colorectal Cancer Screening Uptake Intervention Systematic Reviews: Available Evidence and Lessons Learned for Research and Practice - Young, Belinda-Rose; Gwede, Clement K.; Thomas, Bria; Vázquez-Otero, Coralia; Ewing, Aldenise; Best, Alicia L.; Aguado Loi, Claudia X.; Martinez-Tyson, Dinorah; Schneider, Tali; Meade, Cathy D.; Baldwin, Julie A.; Bryant, Carol (Frontiers in Public Health, 2019)
Background: We examined colorectal cancer screening (CRCS) intervention effectiveness, through the effect sizes associated with: (1) screening modality, (2) intervention level (e.g., client-directed), and (3) intervention component (e.g. client reminders) within published CRCS intervention systematic reviews (SRs). Methods: A search of peer-reviewed CRCS SRs that were written in English was employed utilizing five databases: CINAHL, Cochrane Library, rTIPS, PubMed, and PsycINFO EBSCOHOST. SRs that included CRCS interventions with a randomized controlled trial, quasi-experimental, or single arm design were eligible. Data on effect sizes by screening modality, intervention level, and intervention component were extracted and synthesized. Results: There were 16 eligible CRCS intervention SRs that included 116 studies published between 1986 and 2013. Reviews organized data by CRCS screening modality, or intervention component. Effect size reporting varied by format (i.e., ranges, medians of multiple studies, or effect size per study), and groupings of modalities and components. Overall, the largest effect sizes were for studies that utilized a combination of colonoscopy, fecal occult blood test (FOBT), and sigmoidoscopy as screening options (16-45 percentage point difference). Conclusions: Evidence suggests that CRCS interventions which include a combination of screening modalities may be most effective. This is the first SR to examine effect sizes of published CRCS SRs. However, because some SRs did not report effect sizes and there were tremendous variability reporting formats among those that did, a standard reporting format is warranted. Synthesizing findings can contribute to improved knowledge of evidence-based best-practices, direct translation of findings into policy and practice, and guide further research in CRCS.